Preserving racial hierarchy amidst changing racial demographics: how neighbourhood racial preferences are changing while maintaining segregation. Issue 15 (8th December 2018) - Howell, Junia; Emerson, Michael O.
ABSTRACT: Despite long-term, documented declines in racialized attitudes, racial inequality persists. Scholars have theorized why this dissonance exists but few have empirically demonstrated how views can become more progressive while simultaneously maintaining inequality. The present study uses neighbourhood racial preferences and their influence on racial residential segregation to demonstrate how in a diversifying context residents can become more "accepting" while simultaneously maintaining the racial hierarchy, the opposite of what most of the literature currently assumes. Using data from three distinct sources in the United States, this research finds that U.S. residents are increasingly willing to live amidst diversity yet whites still concentrate in white neighbourhoods. In short, white Americans are more willing to live in diverse neighbourhoods than in the past, but they are not willing to desegregate. We argue this preserves racial inequality. We conclude with a discussion of our findings and their implications for future research and practice.